Differential activities of maize plant elicitor peptides as mediators of immune signaling and herbivore resistance. (2nd December 2020) - Poretsky, Elly; Dressano, Keini; Weckwerth, Philipp; Ruiz, Miguel; Char, Si Nian; Shi, Da; Abagyan, Ruben; Yang, Bing; Huffaker, Alisa
SUMMARY: Plant elicitor peptides (Peps) are conserved regulators of defense responses and models for the study of damage‐associated molecular pattern‐induced immunity. Although present as multigene families in most species, the functional relevance of these multigene families remains largely undefined. While Arabidopsis Peps appear largely redundant in function, previous work examining Pep‐induced responses in maize (Zm) implied specificity of function. To better define the function of individual ZmPeps and their cognate receptors (ZmPEPRs), activities were examined by assessing changes in defense‐associated phytohormones, specialized metabolites and global gene expression patterns, in combination with heterologous expression assays and analyses of CRISPR/Cas9‐generated knockout plants. Beyond simply delineating individual ZmPep and ZmPEPR activities, these experiments led to a number of new insights into Pep signaling mechanisms. ZmPROPEP and other poaceous precursors were found to contain multiple active Peps, a phenomenon not previously observed for this family. In all, seven new ZmPeps were identified and the peptides were found to have specific activities defined by the relative magnitude of their response output rather than by uniqueness. A striking correlation was observed between individual ZmPep‐elicited changes in levels of jasmonic acid and ethylene and the magnitude of induced defense responses, indicating that ZmPeps may collectively regulate immune output through rheostat‐like tuning of phytohormone levels. Peptide structure–function studies and ligand–receptor modeling revealed structural features critical to the function of ZmPeps and led to the identification of ZmPep5a as a potential antagonist peptide able to competitively inhibit the activity of other ZmPeps, a regulatory mechanism not previously observed for this family. Significance Statement: Characterization of the maize plant elicitor peptides reveals new insights into signaling mechanisms not previously observed for this family, including antagonist peptide activity, precursors harboring multiple bioactive peptides and rheostat‐like regulation of phytohormone production and immune output. Together this demonstrates that although the general function of Peps as immunoregulatory signals is widely conserved there are unique signaling features within individual species that are not discoverable by focusing on model plants alone.